Mawah as a Religiously Embedded Economic Institution in Aceh: A Durkheimian Account of Selective Adaptation - Fuadi, Fuadi; Iskandar, Iskandar; Danial, Danial (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
Traditional religious-economic institutions face increasing pressure from modernization and globalization, yet their persistence continues to complicate classical secularization theories. Mawah, a centuries-old Islamic profit-sharing system in Aceh, provides an important case for examining how religion remains embedded in economic life. This study analyzes mawah as both a religious and economic institution through Durkheim's functionalist theory, focusing on its persistence, transformation, and contemporary relevance as an Islamic economic alternative. This study employed a qualitative case study design with ethnographic elements, conducted in Pidie Jaya and Aceh Besar districts. Data were collected through focus group discussions, semi-structured interviews, and direct observations, complemented by recent scholarly literature. Analysis combined inductive coding with Durkheim’s concepts of solidarity, ritual, and collective effervescence, alongside Islamic jurisprudential principles such as al-adah muhakkamah (custom as a source of law). This study found that mawah persists as a post-secular institution through selective adaptation. Agricultural practices demonstrate rationalization tendencies, often resembling contractual arrangements, yet still operate within Islamic ethical frameworks of justice, trust, and collective welfare. By contrast, livestock-based mawah retains strong ritual dimensions through communal prayers, shared meals, and religious mediation, exemplifying collective effervescence. Trust networks rooted in religious authority and community membership remain central, providing moral legitimacy that purely instrumental arrangements cannot offer. This study contributes to sociology of religion by showing that religious institutions adapt through differential secularization rather than uniform decline. For policymakers, mawah illustrates how culturally grounded Islamic economic institutions can strengthen local development strategies while preserving social solidarity and religious authenticity.